PROTOCOL: Gender transformative approaches in agriculture for women's empowerment: a systematic review - Singh, S.; Mohan, A.; Saran, A.; Puskur, Ranjitha; Mishra, A.; Etale, L.; Cole, Steven M.; Masset, E.; Waddington, Hugh Sharma; MacDonald, H.; White, Howard (Wiley, 2022)
This is the protocol for a Campbell systematic review. The objective of this systematic review is to assess the effectiveness of interventions with gender transformative approach (GTA) components in improving women's empowerment in low- and middle-income countries, and to curate evidence on the mechanisms through which GTA works to improve women's empowerment in agriculture.